2020
DOI: 10.2147/ijn.s243548
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeted Nanobubbles Carrying Indocyanine Green for Ultrasound, Photoacoustic and Fluorescence Imaging of Prostate Cancer</p>

Abstract: Objective: To construct prostate-specific membrane antigen (PSMA)-targeting, indocyanine green (ICG)-loaded nanobubbles (NBs) for multimodal (ultrasound, photoacoustic and fluorescence) imaging of prostate cancer. Methods: The mechanical oscillation method was used to prepare ICG-loaded photoacoustic NBs (ICG NBs). Then, PSMA-binding peptides were connected to the surface of ICG NBs using the biotin-avidin method to make targeted photoacoustic NBs, namely, PSMAP/ICG NBs. Their particle sizes, zeta potentials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…We also confirmed that polypyrrole nanoparticles provided a substantially higher PA signal at the same experimental conditions than a commercial ICG, which is broadly used as a photoacoustic tracer or label [ 43 , 44 , 45 ]. The intent of the study was indeed the physical characterization of the particles, which may enable further optimization of their preparation for future applications.…”
Section: Discussionsupporting
confidence: 71%
“…We also confirmed that polypyrrole nanoparticles provided a substantially higher PA signal at the same experimental conditions than a commercial ICG, which is broadly used as a photoacoustic tracer or label [ 43 , 44 , 45 ]. The intent of the study was indeed the physical characterization of the particles, which may enable further optimization of their preparation for future applications.…”
Section: Discussionsupporting
confidence: 71%
“…Since recognizing its link to cancer, PSMA has emerged as an attractive target for the development of diagnostic tools via PA imaging. 157–160…”
Section: Targeted Contrast Agents For Photoacoustic Imagingmentioning
confidence: 99%
“…13a). 158 To achieve this, authors loaded phospholipid-based bubbles with ICG and appended PSMA-binding peptide (WQPDTAHHWATL) via a biotin–streptavidin linkage. After obtaining promising in vitro results, they sought to investigate the PA enhancement of their nanobubbles, PSMAP/ICG NBs, in vivo .…”
Section: Targeted Contrast Agents For Photoacoustic Imagingmentioning
confidence: 99%
“…This nanoparticle effectively bound to PSMA-positive prostate cancer cells, LNCaP cellsand C4-2 cells, and also enhancedthe imaging potential of multimodal techniques. Ultimately, this multimodal contrast agent was found to helpwith prostate cancer diagnosis and assessment [ 169 ]. A study designed the USF contrast agents (ICG-NPs and ExiTron nano 12000) with particle sizes ranging from 70 nm to 330 nm and administered themintravenously to understand the distribution of contrast agents in tumor and normal tissues including liver, kidney, and spleen.…”
Section: Nanomaterials and Their Clinical Applicationmentioning
confidence: 99%